Sericin from mulberry and non-mulberry silk using chemical-free degumming. Issue 10 (26th September 2022) - Kalita, Monalisa; Allardyce, Benjamin J.; Sankaranarayanan, Kamatchi; Devi, Dipali; Rajkhowa, Rangam
Abstract: In this study we report the extraction and characterization of sericin using water alone, from two non-mulberry silks - Antheraea assamensis (A. assamensis) and Philosamia ricini (P. ricini) compared with Bombyx mori (B. mori) silk. Degumming at 130 °C offered the highest sericin removal for A. assamensis ; P. ricini had the lowest sericin removal among the varieties, because of its lower overall sericin content. Along with sericin degumming, fiber tensile properties were also reported. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) of sericin revealed minimal sericin degradation even for degumming temperatures above 100 °C. The spectra from Fourier Transform Infrared Spectroscopy (FTIR) confirmed random coil motifs for B. mori sericin but a higher proportion of β-sheets in A. assamensis and P. ricini sericin which is likely to contribute to their lower water solubility. Thus, high temperature, water-based processing can be a potential approach for chemical- free degumming of silk fibers and to obtain high molecular weight sericin for different biomaterial applications.